Character and Islamic Values Integration in the Merdeka Curriculum: Its Impact on Students’ Learning Discipline in Batam - Misbah; Eliza Farahsiba Saleh (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
ABSTRACT This study is motivated by the growing importance of strengthening character education and Islamic educational values in the implementation of the Merdeka Curriculum, which emphasizes a balance between academic achievement and students’ moral formation. This research aims to analyze the influence of character education integration and Islamic educational values on students’ learning discipline in senior high schools in Batam City. The study employed a quantitative approach using an associative survey design involving 330 students randomly selected from a population of 1,892 students across three schools: SMA Negeri 4 Batam, SMA Kartini, and SMA Integral Hidayatullah. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 26. The results indicate that character education integration (β = 0.476; p < 0.001) and Islamic educational values (β = 0.316; p < 0.001) both have a positive and significant effect on students’ learning discipline, with a combined explanatory power of 47.5% (R² = 0.475). These findings demonstrate that learning discipline is more effectively shaped through the synergistic internalization of universal moral values and Islamic principles within school culture. This study contributes to Islamic education scholarship and national curriculum policy by providing empirical evidence that the effectiveness of the Merdeka Curriculum is significantly enhanced when character education and Islamic educational values are integrated as a unified framework for shaping students’ learning discipline. The study concludes that the success of the Merdeka Curriculum depends not only on academic content but also on the consistent integration of moral and spiritual values in everyday school practices.   ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya penguatan pendidikan karakter dan nilai-nilai pendidikan Islam dalam pelaksanaan Kurikulum Merdeka yang menekankan keseimbangan antara pencapaian akademik dan pembentukan moral peserta didik. Tujuan penelitian ini adalah menganalisis pengaruh integrasi pendidikan karakter dan nilai-nilai pendidikan Islam terhadap kedisiplinan belajar siswa SMA di Kota Batam. Penelitian ini menggunakan pendekatan kuantitatif dengan desain asosiatif melalui survei terhadap 330 siswa yang dipilih secara acak dari populasi 1.892 siswa di tiga sekolah, yaitu SMA Negeri 4 Batam, SMA Kartini, dan SMA Integral Hidayatullah. Data dikumpulkan menggunakan kuesioner skala Likert yang telah teruji validitas dan reliabilitasnya, kemudian dianalisis dengan regresi linier berganda menggunakan SPSS 26. Hasil penelitian menunjukkan bahwa integrasi pendidikan karakter (β = 0,476; p < 0,001) dan nilai-nilai pendidikan Islam (β = 0,316; p < 0,001) berpengaruh positif dan signifikan terhadap kedisiplinan belajar siswa, dengan kontribusi bersama sebesar 47,5% (R² = 0,475). Temuan ini menegaskan bahwa kedisiplinan belajar lebih efektif dibentuk melalui internalisasi sinergis antara nilai-nilai moral universal dan prinsip-prinsip Islam dalam budaya sekolah. Penelitian ini memberikan kontribusi bagi studi pendidikan agama dan kebijakan kurikulum nasional dengan menunjukkan secara empiris bahwa keberhasilan Kurikulum Merdeka semakin optimal ketika pendidikan karakter dan nilai-nilai Islam diintegrasikan secara terpadu sebagai kerangka pembentukan kedisiplinan belajar. Simpulan penelitian menyatakan bahwa keberhasilan Kurikulum Merdeka tidak hanya ditentukan oleh aspek akademik, tetapi juga oleh integrasi nilai moral dan spiritual secara konsisten dalam kehidupan sekolah.